Biocompatible Liquid Embolic for the Treatment of Microvascular Hemorrhage - Hyeongseop Keum; Jinjoo Kim; Zefu Zhang; Erin Graf; Hassan Albadawi; Rahmi Oklu (Advanced Science, 2024)
Abstract Persistent or recurrent bleeding from microvessels inaccessible for direct endovascular intervention is a major problem in medicine today. Here, an innovative catheter‐directed liquid embolic (P‐LE) is bioengineered for rapid microvessel embolization to treat small vessel hemorrhage. Tested in rodent, porcine, and canine animal models under normal and coagulopathic conditions, P‐LE outperformed clinically used embolic materials in both survival and non‐survival experiments, effectively occluding vessels as small as 40 microns with no signs of recanalization. P‐LE occlusion is independent of the coagulation cascade, and its resistance to displacement is ≈ 8 times greater than systolic blood pressure. P‐LE is also found to be biocompatible and x‐ray visible and does not require polymerization or a chemical reaction to embolize. To simulate the clinical scenario, acute microvascular hemorrhage is created in the pig kidney, liver, or stomach; these are successfully treated with P‐LE achieving immediate hemostasis. Furthermore, P‐LE is found to be bactericidal to highly resistant patient‐derived bacteria, suggesting that P‐LE may also protect against infectious complications that may occur following embolization procedures. P‐LE is safe, easy to use, and effective in treating ‐microvessel hemorrhage.